Breast Cancer Knowledge as a Predictor of Regular Breast Self-Examination among Women Aged 20–49 in Ejisu Municipality, Ghana - Joseph Oteng; Bemhemba Iba; Isaac John Umaru (Darul Yasin Al Sys, 2026)
Breast cancer is the leading cause of cancer-related morbidity and mortality among women globally, and in low-resource settings such as Ghana, breast self-examination (BSE) remains a cost-effective strategy for early detection, yet a persistent gap exists between awareness and consistent practice. This study assessed women’s knowledge of breast cancer and examined whether knowledge predicts regular BSE practice among women aged 20–49 years in Ejisu Municipality, Ghana. A community-based cross-sectional survey was conducted among 635 women selected using systematic random sampling. Data were collected using a structured questionnaire assessing socio-demographic characteristics, breast cancer knowledge, and BSE practice, with knowledge scores categorized as low, moderate, or high using tertiles. Descriptive statistics, chi-square tests, and multivariate logistic regression were applied, with statistical significance set at p < 0.05. The mean age of participants was 32.9 ± 7.1 years, and most (67.2%) demonstrated high breast cancer knowledge, primarily sourced from health professionals (53.5%). Although 72.0% had heard of BSE, only 32.1% practiced it monthly as recommended, with key barriers including lack of knowledge of the correct technique (47.8%) and fear of detecting a lump (22.8%). Knowledge level was significantly associated with regular BSE practice (χ² = 42.57, p < 0.001), and multivariate analysis showed that women with high knowledge were more than three times as likely to perform regular BSE (AOR = 3.45, 95% CI: 2.18–5.52, p < 0.001) compared with those with low knowledge. Tertiary education (AOR = 2.26, p = 0.004) and receiving information from health workers (AOR = 2.06, p = 0.008) also independently predicted regular BSE. The study concludes that breast cancer knowledge is a strong predictor of regular BSE practice; despite relatively high awareness, routine BSE remains low due to skill-related and psychological barriers. Strengthening health education with practical demonstrations and integrating BSE counseling into routine clinical care and community outreach may enhance preventive behavior and contribute to earlier breast cancer detection.